Unzipping carbon nanotubes into nanoribbons upon oxidation : a first-principles study - Li, Feng (2013)
First-principles calculations are performed to investigate the unzipping mechanism of carbon nanotubes (CNTs) into narrow graphene nanoribbons (GNRs) upon oxidation. By treating possible adsorptive structures, we found that, upon further oxidation, epoxy pairs tear the CNT up with an initial energy barrier of 0.59 eV (armchair) and 0.60 eV (zigzag), and the following steps of unzipping CNT become much easier because of the stress induced by the carbonyl pair. However, for zigzag CNTS, the unzipped edge structures of nanoribbons cannot be controlled, because of the similar stability of different oxidation process, which means zigzag CNTs should be avoided in producing high-quality GNRs.